2017
DOI: 10.4012/dmj.2016-157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of core thickness and artificial aging on the biaxial flexural strength of different all-ceramic materials: An <i>in-vitro</i> study

Abstract: The purpose of this study was to investigate the flexural strength of all-ceramics with varying core thicknesses submitted to aging. In-Ceram Alumina (IC), IPS e.max Press (EM) and Katana (K) (n=40), were selected. Each group contained two core groups based on the core thickness as follows: IC/0.5, IC/0.8, EM/0.5, EM/0.8, K/0.5 and K/0.8 mm in thickness (n=20 each). Ten specimens from each group were subjected to aging and all specimens were tested for strength in a testing machine either with or without being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Gierthmuehlen et al 26 also demonstrated that fracture loads of ceramics with thicknesses of 1.5 mm and 1 mm were similar, suggesting that 1 mm ceramic thickness was reliable even in the posterior restorations. Dikicier et al 27 demonstrated that the fracture strength of zirconia increased with the thickness (from 0.5 mm to 0.8 mm), and both were not affected by aging. The fracture strength of the zirconia increases with the occlusal thickness; however, even thinner zirconia restorations have adequate fracture strength, reported by Yin et al 28 demonstrating a fracture strength greater than 1500 N and 2500 N in 0.5 mm and 1.00 mm zirconia, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Gierthmuehlen et al 26 also demonstrated that fracture loads of ceramics with thicknesses of 1.5 mm and 1 mm were similar, suggesting that 1 mm ceramic thickness was reliable even in the posterior restorations. Dikicier et al 27 demonstrated that the fracture strength of zirconia increased with the thickness (from 0.5 mm to 0.8 mm), and both were not affected by aging. The fracture strength of the zirconia increases with the occlusal thickness; however, even thinner zirconia restorations have adequate fracture strength, reported by Yin et al 28 demonstrating a fracture strength greater than 1500 N and 2500 N in 0.5 mm and 1.00 mm zirconia, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that monolithic zirconia crowns exhibit greater fracture resistance than bilayered ones [16] and that the thickness of full contour ceramic restorations influences fractures resistance [17]. According to the ISO 6872:2015 [7], specimens for the biaxial flexural strength test should have a diameter of 12 mm and a thickness of 1.2 mm, but the literature presents several papers that used Y-TZP specimens or other ceramics in dimensions other than those required by ISO for biaxial flexural tests [18][19][20][21][22][23][24][25][26]. Due to a limitation of the fatigue equipment in load application levels, this work used 0.8 mm thick samples after monotonically testing samples of varying thicknesses of 0.6 to 1.4 mm in a pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…As for Katana, studies reported resistance against aging and high physical properties such as low PT, high flexural strength even with 0.2 mm thickness [28,30]. Also, Dikicier et al [36] demonstrated that flexural strength and fracture strength of Katana zirconia increased with the thickness of the material (from 0.5 mm to 0.8mm) and both of them was not affected by aging. In contrast, despite samples with higher thickness, Katana exhibited lower features compared to other materials.…”
Section: Discussionmentioning
confidence: 97%